HUBUNGAN PENGETAHUAN PEMBERIAN MP-ASI DAN PERILAKU KELUARGA SADAR GIZI TERHADAP KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN DI PUSKESMAS POLOKARTO - Rohmandani, Indah Dwi (Jurnal Kesehatan Masyarakat, 2024)
Stunting can be seen from the condition where children experience impaired growth as a result of chronic nutritional problems. Several factors can cause stunting, including lack of knowledge of complementary feeding and nutrition awareness behavior. This study aims to determine the relationship of complementary feeding knowledge and nutrition awareness family behavior to the incidence of stunting in children aged 6-24 months at Polokarto Health Center. The research method used was observational analytic with a cross-sectional approach. The results of the knowledge study showed a p-value = 0.003, meaning that there was a relationship between knowledge of complementary feeding with the incidence of stunting in children aged 6-24 months at the Polokarto Health Center. The results of behavioral research showed a p-value = 0.001, which means that there is a relationship between nutrition-conscious family behavior and the incidence of stunting in children aged 6-24 months at Puskesmas Polokarto. In this study it can be concluded that there is a relationship between knowledge of complementary feeding and nutrition-conscious family behavior on the incidence of stunting in children aged 6-24 months at Puskesmas Polokarto.